Glycosidic Bond Expanded Cyclic Oligosaccharides: Synthesis and Host–Guest Binding Property of a Cyclic Pentasaccharide - Samanta, Gopal Ch (ACS Omega, 2018)
[Image: see text] A new cyclic pentasaccharide comprising an oxymethylene glycosidic bond connecting the individual α-d-glycopyranoside monomers is synthesized through cycloglycosylation of a linear pentasaccharide precursor, which, in turn, is synthesized through the block glycosylation method. Molecular modeling shows that the 30-membered macrocyclic pentasaccharide is a distorted ellipsoid structure, with the lower and upper rims occupied by secondary and primary hydroxyl groups, respectively. Following the synthesis, the microenvironment of the cyclic pentasaccharide is assessed through thermodynamic evaluation upon complexation with 1-aminoadamantane in an aqueous solution, which shows the formation of ∼1:2 host-to-guest complex and a binding affinity of 10 500 (±425) M(–1). Synthesis and assessment of the host–guest binding property of the new glycosidic bond expanded cyclic pentasaccharide are presented.